Low cost fabrication of micromixer and microchamber for microfluidic lab-on-chip - Uda, Hashim, Prof. Dr.; Tijjani Adam, Shuwa; M. Wesam, Al-Mufti; Ling, Peter Jie Lung; Shahrul Aizzam, Ariffin (Institute of Electrical and Electronic Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/